2010
DOI: 10.1016/j.cortex.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Margaret Kennard (1899–1975): Not a ‘Principle’ of brain plasticity but a founding mother of developmental neuropsychology

Abstract: According to the 'Kennard Principle', there is a negative linear relation between age at brain injury and functional outcome. Other things being equal, the younger the lesioned organism, the better the outcome. But the 'Kennard Principle' is neither Kennard's nor a principle. In her work, Kennard sought to explain the factors that predicted functional outcome (age, to be sure, but also staging, laterality, location, and number of brain lesions, and outcome domain) and the neural mechanisms that altered the les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 82 publications
(75 reference statements)
0
27
0
1
Order By: Relevance
“…Although not an absolute predictor of functional recovery (Kolb et al, 2000, Giza and Prins, 2006, Dennis, 2010), it has long been appreciated that juvenile brains are often more resilient to injury than mature brains (Broca, 1865, Kennard, 1936), however the underlying mechanisms for these profound differences in neuronal plasticity and functional recovery are just beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although not an absolute predictor of functional recovery (Kolb et al, 2000, Giza and Prins, 2006, Dennis, 2010), it has long been appreciated that juvenile brains are often more resilient to injury than mature brains (Broca, 1865, Kennard, 1936), however the underlying mechanisms for these profound differences in neuronal plasticity and functional recovery are just beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…1, Models E-J). Because children with later-onset injury typically have some measured or historical information about pre-injury development, delayed effects (what Kennard identified as growing into a deficit, discussed in Dennis, 2010) can be identified, whereby deficits not apparent at the time of the injury emerge with increasing time since injury, or as the brain matures (Luciana, 2003). Functional outcome is measured by Intercepts 1 and 2, and Slope 3, but also by indices of the effect of acquired lesion on loss and recovery of previously developed skills and new skill development.…”
Section: When To Assessmentioning
confidence: 99%
“…This idea arose in part from misreading of Kennard’s work in the 1930s and 1940s (see Dennis, 2010). Kennard had shown that age, but also factors other than age, predicted outcome after early brain lesions.…”
Section: Introductionmentioning
confidence: 99%